Analisis Semantik Sifat-Sifat Yang Merujuk kepada Perempuan dalam Al-Quran - Nur Saadah Hamisan @Khair; Norullisza Khosim; Norfarhana Ahmad Ghafar (Penerbit USIM, 2025)
International Conference of Quran as Foundation of Civilization (SWAT 2025) : Maqasid al-Quran and the Madani Vision: A Guiding Light for Regional Serenity and Global Unity Organized by : Faculty of Quranic and Sunnah Studies, in collaboration with Nasyrul Quran and Daffodil International University, Bangladesh. Date:12-13 November 2025